Early Adversity and Accelerated Brain Aging: A Mini-Review - Chaudhari, Pratik R.; Singla, Aastha; Vaidya, Vidita A. (Frontiers in Molecular Neuroscience, 2022)
Early adversity is an important risk factor that influences brain aging. Diverse animal models of early adversity, including gestational stress and postnatal paradigms disrupting dam-pup interactions evoke not only persistent neuroendocrine dysfunction and anxio-depressive behaviors, but also perturb the trajectory of healthy brain aging. The process of brain aging is thought to involve hallmark features such as mitochondrial dysfunction and oxidative stress, evoking impairments in neuronal bioenergetics. Furthermore, brain aging is associated with disrupted proteostasis, progressively defective epigenetic and DNA repair mechanisms, the build-up of neuroinflammatory states, thus cumulatively driving cellular senescence, neuronal and cognitive decline. Early adversity is hypothesized to evoke an ‘allostatic load’ via an influence on several of the key physiological processes that define the trajectory of healthy brain aging. In this review we discuss the evidence that animal models of early adversity impinge on fundamental mechanisms of brain aging, setting up a substratum that can accelerate and compromise the time-line and nature of brain aging, and increase risk for aging-associated neuropathologies.